CHI '04 Extended Abstracts on Human Factors in Computing Systems 2004
DOI: 10.1145/985921.986058
|View full text |Cite
|
Sign up to set email alerts
|

INTERACTING with sketched interface designs

Abstract: Digital hand-drawn sketches provide a new and unique way of interacting with a prototype user interface design while it is still rendered as a sketch. The successful use of prototypes and scenarios for exploring design ideas is well documented. Hand-sketched designs have also been found preferable to formal diagrams during early design. The study reported here shows that interacting with digital sketches adds an exciting new dimension to the interface design process, we found that people do more revisions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 11 publications
1
45
0
2
Order By: Relevance
“…The fidelity is said to be low if the prototype representation only partially evokes the final UI without representing it in full details. Between high-fidelity (hi-fi) and low-fidelity (low-fi) [17] exists medium-fidelity (me-fi) [9]. We usually observe that a UI prototype only involves one representation type, i.e.…”
Section: Related Workmentioning
confidence: 99%
“…The fidelity is said to be low if the prototype representation only partially evokes the final UI without representing it in full details. Between high-fidelity (hi-fi) and low-fidelity (low-fi) [17] exists medium-fidelity (me-fi) [9]. We usually observe that a UI prototype only involves one representation type, i.e.…”
Section: Related Workmentioning
confidence: 99%
“…Using hand-drawn designs in this way has the demonstrated advantages over conventional software diagramming tools of flexibility, encouragement of exploratory design, and support for collaborative annotation and design review [2,26,29]. Conventional diagramming tools have been shown by many studies to suffer from premature commitment to particular design artefacts and choices; over-constraint of user actions; high viscosity (making designs hard to change); stifling of creativity; and limited collaborative design and review support [29]. As many studies have shown, sketchingbased design tools for a wide range of diagram-centric tasks offer ways of combining the advantages of paperbased and whiteboard-based design with those of computer-based diagramming tools [2,5,7,11,15,20,29].…”
Section: Motivationmentioning
confidence: 99%
“…Conventional diagramming tools have been shown by many studies to suffer from premature commitment to particular design artefacts and choices; over-constraint of user actions; high viscosity (making designs hard to change); stifling of creativity; and limited collaborative design and review support [29]. As many studies have shown, sketchingbased design tools for a wide range of diagram-centric tasks offer ways of combining the advantages of paperbased and whiteboard-based design with those of computer-based diagramming tools [2,5,7,11,15,20,29]. To date, though, most such research has focused on supporting sketching-based input in a narrow range of design tasks i.e.…”
Section: Motivationmentioning
confidence: 99%
See 2 more Smart Citations